(untitled) (Research, Society and Development, 2025)
The Brazilian plant Erythrina mulungu Mart. ex Benth, from the Fabaceae family, is used in traditional medicine as a natural sedative, aiding in the treatment of stress, anxiety, and depression. Its extracts, typically obtained from the bark, fruits, and leaves, have well-documented pharmacological properties, especially hydroalcoholic extracts. However, the therapeutic effects and toxicity of this plant remain poorly explored. This study aimed to investigate the potential therapeutic applications of Erythrina mulungu and its fractions through a literature review using databases such as SCIELO, MEDLINE, BIREME, PubMed, and Google Scholar. It was found that Erythrina species are rich in tetracyclic alkaloids with curare-like activity, inducing muscle paralysis. Compounds such as erythrartine, erythravine, and their derivatives exhibited anxiolytic effects comparable to benzodiazepines. Additionally, activities in the central nervous system have been documented, including neurotransmitter receptor modulation and anticonvulsant, sedative, and amnesic effects. The plant has also demonstrated antibacterial and antinociceptive properties. Despite this evidence, the biological activities of E. mulungu remain underexplored, highlighting the need for further studies to better understand its mechanisms of action, safety, and therapeutic applications.